CAP ou pas CAP ? Analyse d’un dispositif de collaboration - Frédéric Yvon; Dimitri Skopelitis (Recherches en Éducation)
This text focuses on a collaborative system in Secondary School : the Professional Learning Community (PLC) much known as a collaborative plan. It traces the development of a PLC in the Canton of Geneva over several years. In the scientific works, PLC is seen as a procedural plan, which could be simply implemented to guide and frame the work of teachers. On the contrary, the article insists on the importance of taking into account the context in order to support the development of collective activity.